Usabilidade de aplicativos móveis voltados para a saúde acopláveis a diferentes equipamentos vestíveis - Dominguete, Gustavo Lopes (2020)
The use of technological resources in the health domain has increased significantly. These technologies can help to obtain accurate data quickly to support decision making, and wearable systems are among the systems that have gained ground in this context. The development of systems that support people’s health must aim at good usability and reliability. Wearable systems involve specific usability issues related to the fact that users have more direct physical contact with the devices. Thus, there is a great interest in studying ways to facilitate the use and to ensure the reliability of wearable systems to prevent harmful interference with the user’s health. Wearable health systems usually contain built-in sensors or include connections to external equipment, with features for users to use data in different ways. Systems that allow flexibility in connecting with different wearable equipment, especially mobile applications, offer many advantages for users. However, with the possibility of using applications coupled with various wearable equipment and sensors, there is a more significant challenge for the usability of the applications, considering the diversity of data types and the process of coupling the sensors and other components of a wearable system. Given these challenges, this research aimed to answer the following question: “Which usability heuristics can support the design of the connection process in applications coupled to different wearable health monitoring equipment?”. To answer this question, the study performed a usability evaluation with 30 users, to evaluate a piece of wearable equipment created in the research used with three physical activity monitoring applications present in the market, which allow the coupling with several types of wearable equipment. The analysis of the usability problems encountered in these tests led to the definition of five new heuristics to assist the development of interactive systems to support the connection between wearable health equipment and applications. To assess the use of heuristics, three sessions of heuristic evaluations were conducted on a proof-of-concept application with experts, with corrections between sessions. The evaluations of the existing applications resulted in 714 usability problems. Of these problems, 256425 were related to the coupling between the wearable equipment and the application. The heuristic evaluations found a total of 215 usability problems, 79 in the first, 74 in the second and 62 in the third. The results indicated that the new heuristics enabled finding problems in the evaluation of the proof-of-concept application. The number of problems related to the heuristics created in this research decreased in the second and third evaluations after corrections made using the heuristics. The present work contributed to the identification of usability problems existing in the coupling of wearable equipment and applications that can be coupled with different types of wearable equipment and the proposal and evaluation of the use of a set of five new heuristics. It is expected that, with the help of these heuristics, it will be possible to develop wearable systems for use in the health context with better usability in applications with flexibility in the use of different sensors.